Knowledge Dynamics and Absorptive Capacity: Shaping Innovation Performance in the Service Business of Small and Medium-Sized Enterprises - Siregar, Onan Marakali; Ridho, Hatta; Nasution, Muhammad Arifin; Nasution, Muhammad Dharma Tuah Putra (International Review of Management and Marketing, 2024)
This study investigates how knowledge breadth and depth impact innovation within the service industry, drawing from the Knowledge-Based View. Using quantitative methods, it explores the relationship among knowledge breadth, depth, and absorptive capacity in driving innovation performance, especially in small and medium-sized enterprises (SMEs). With active involvement from 237 SME owners and managers, the results reveal significant effects in the pathways from absorptive capacity to innovation performance and from knowledge breadth to absorptive capacity, highlighting their significant influence. Similarly, the path from knowledge breadth to innovation performance demonstrates a notable impact, emphasizing the importance of having a wide range of knowledge. Upon examining the paths from knowledge depth to absorptive capacity and from knowledge depth to innovation performance, the significant effects are confirmed. This study stresses the critical role of both knowledge breadth and depth in shaping organizational absorptive capacity and innovation performance, offering practical insights for businesses. It also emphasizes the pivotal role of absorptive capacity and the advantages of utilizing external knowledge.The practical recommendations advocate for tailored strategies that balance precision to achieve favorable innovation outcomes. While providing valuable contributions, the study acknowledges certain limitations and suggests potential directions for future research.